2009
DOI: 10.1027/1618-3169.56.6.434
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Fragile

Abstract: Numerous studies suggest that processing verbal materials containing negations slows down cognition and makes it more error-prone. This suggests that processing negations affords relatively nonautomatic processes. The present research studied the role of two automaticity features (processing speed and resource dependency) for negation processing. In three experiments, we tested the impact of verbal negations on affective priming effects in the Affect Misattribution Paradigm. Going beyond previous work, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 110 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Selfcontrol (e.g., Lattimore & Maxwell, 2004 ;Wegner, Erber, & Zanakos, 1993 ), processing of negated stimuli (Deutsch et al 2009 ), social judgments and attributions (Gilbert et al, 1988 ;Krull & Erickson, 1995 ;Trope & Alfi eri, 1997 ), moral judgments (Greene, Morelli, Lowenberg, Nystrom, & Cohen, 2008 ), and general reasoning (De Neys, 2006 ) have all proven to be impaired by cognitive load in ways that are consistent with the RIM's predictions. The idea that working memory resources may also play a role in refl ective processing has been tested in several studies, both by comparing individuals with dispositionally high or low working memory capacities (Hofmann, Gschwendner, Friese, Wiers, & Schmitt, 2008 ;Thush et al, 2008 ) and by specifi cally taxing resources of working memory (Deutsch et al, 2009 ). The conceptualization of working memory as "a domain-free limitation in ability to control attention" (Engle, 2002 , p. 19) points to the conclusion that the effects of attentional cognitive load manipulations on refl ective processing may be mediated by working memory capacity.…”
Section: Motivation and Opportunitysupporting
confidence: 64%
See 4 more Smart Citations
“…Selfcontrol (e.g., Lattimore & Maxwell, 2004 ;Wegner, Erber, & Zanakos, 1993 ), processing of negated stimuli (Deutsch et al 2009 ), social judgments and attributions (Gilbert et al, 1988 ;Krull & Erickson, 1995 ;Trope & Alfi eri, 1997 ), moral judgments (Greene, Morelli, Lowenberg, Nystrom, & Cohen, 2008 ), and general reasoning (De Neys, 2006 ) have all proven to be impaired by cognitive load in ways that are consistent with the RIM's predictions. The idea that working memory resources may also play a role in refl ective processing has been tested in several studies, both by comparing individuals with dispositionally high or low working memory capacities (Hofmann, Gschwendner, Friese, Wiers, & Schmitt, 2008 ;Thush et al, 2008 ) and by specifi cally taxing resources of working memory (Deutsch et al, 2009 ). The conceptualization of working memory as "a domain-free limitation in ability to control attention" (Engle, 2002 , p. 19) points to the conclusion that the effects of attentional cognitive load manipulations on refl ective processing may be mediated by working memory capacity.…”
Section: Motivation and Opportunitysupporting
confidence: 64%
“…Evidence supporting this logic comes from the Bona Fide Pipeline task (Fazio, Jackson, Dunton, & Williams, 1995 ), which was used in a study by Deutsch, Gawronski, and Strack ( 2006 ), who showed that positive prime words facilitated categorization of positive targets even when the prime was negated, whereas both negated and nonnegated negative prime words facilitated categorization of negative target. Although this effect is not universal (Deutsch et al, 2009 ), it provides evidence that impulsive associations are what implicit attitude procedures measure. Procedures used to change implicit attitudes, such as automatic stereotype reduction training (Kawakami, Dovidio, Moll, Hermsen, & Russin, 2000 ), can also benefi t from the implications of the RIM's structure.…”
Section: Knowledge and Action: Bidirectional Connectionsmentioning
confidence: 94%
See 3 more Smart Citations